Bosque de Don Margarito = Margarito's forest - Carter, Andy, 1948-; Havens, Allison; Mejia, Omar; Carter, Andy, 1948-; Carter, Andy, 1948-. ([United States?] : Hard Ball Press, 2016)
Margarito's Forest, a bilingual book in English and Spanish with excerpts in K'iche', is based on the life of Don Margarito Esteban Alvarez Velazquez as told by his daughter, Dona Maria Guadalupe. It is a story of Maya culture and wisdom passed from one generation to the next. As the devastating effects of climate change become clear, Don Margarito's life and the ways of the Maya offer timely wisdom for a planet in peril.
Translated from the English.
In statement of responsibility "translations" is misspelled as tranlations.
Text mainly in English and Spanish with some Quiche.
Americas Award commended title, 2017.
Keywords: Mayas -- Guatemala -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Gardening -- Juvenile fiction; Families -- Juvenile fiction; Wisdom -- Juvenile fiction; Biographical fiction; Fiction; Juvenile works; Biographical fiction